Improvement of interpretation in cystic fibrosis clinical laboratory reports: longitudinal analysis of external quality assessment data - Berwouts, Sarah (Nature Publishing Group, 2012)
Participation in external quality assessment (EQA) is a key element of quality assurance in medical laboratories. In genetics EQA, both genotyping and interpretation are assessed. We aimed to analyse changes in the completeness of interpretation in clinical laboratory reports of the European cystic fibrosis EQA scheme and to investigate the effect of the number of previous participations, laboratory accreditation/certification status, setting and test volume. We distributed similar versions of mock clinical cases to eliminate the influence of the difficulty of the clinical question on interpretation performance: a cystic fibrosis patient (case 1) and a cystic fibrosis carrier (case 2). We then performed a retrospective longitudinal study of reports over a 6-year period from 298 participants for case 1 (2004, 2008, 2009) and from 263 participants for case 2 (2006, 2008, 2009). The number of previous participations had a positive effect on the interpretation score (P<0.0001), whereas the laboratory accreditation/certification status, setting and test volume had no effect. Completeness of interpretation improved over time. The presence of the interpretation element ‘requirement for studying the parents to qualify the genotype' increased most (from 49% in 2004 to 93% in 2009). We still observed room for improvement for elements that concerned offering testing for familial mutations in relatives and prenatal/preimplantation diagnosis (16% and 24% omission, respectively, for case 1 in 2009). Overall, regular participation in external quality assessment contributes to improved interpretation in reports, with potential value for quality of care for patients and families by healthcare professionals involved in genetic testing.